COMPLEXITY OF COMBINING ELEMENTS OF STRUCTURAL GROUPS OF RHYTHMIC GYMNASTICS AS A CRITERION OF PERFORMANCE SKILL OF SPORTSWOMAN - Medvedeva E.N.; Terekhina R.N.; Viner I.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to specify the factors of coordination complexity of combining elements of rhythmic gymnastics structural groups, which contribute to the objectification of the assessment of the performance skills of athletes. Methods and structure of the study. To identify biomechanical factors of complexity of combining elements of various structural groups, a set of pedagogical and synchronized biomechanical techniques was used: analysis of special literature and program documents, pedagogical observations, a survey, a method of contactless study of a video sequence of movements in combination with surface electromyography and stabilometry, designing, pedagogical experiment, methods of mathematical statistics. Results and conclusions. The article substantiates the position that characterizes the possibility of an objective evaluation of the complexity of combined elements and the ranking of athletes by the level of their execution skills. The author’s approach to determining the technical value of combined elements on the basis of taking into account the biomechanical laws of technique creates conditions for increasing the complexity and compositional perfection of competitive routines in accordance with modern requirements of rhythmic gymnastics. The purposeful development of the technical components of combined elements ensures the implementation of a perspective-prognostic approach to the formation of execution skills of rhythmic gymnastics athletes.